A lei jurídica e as leis da liberdade: o papel do direito em relação à moral - Pagno, Luana (2017)
The main objective of this dissertation is to understand the classification of juridical laws in the ambit of moral laws, proposed by Kant, in order to investigate what this classification represents to think the relation between moral and law. With the intention to reach this aim, the master work presents, first, a contextualization of morality and right, and their respective laws, with the purpose of demonstrating why this classification is intriguing. After, the concept of moral laws and juridical laws is presented, from the bibliographic review of the Kantian works, mainly of The Metaphysics of Morals with the perspective of understanding the definition of these laws and the role attributed to them. This stage is importante, as far as allows to comprehend how juridical laws can be a subclass of moral laws, and the relation of these laws with the freedom. Posteriorly, the dissertation focuses on analyzing the role and the emergence of juridical law in the scope of right, in order to understand how it can have a function related to legality and morality concomitantly. From this exposition it is possible to include the role of juridical law in relation to freedom. After this stage, the máster work presents the study of some principles that grounds the duties of law, approaching its relation with the juridical law, as well as, exposes the constituent elements of the rule of law, with the purpose of proving how the right and the juridical law are related to freedom and, as this tends to a moral perspective. From this process it is possible to conclude that the term moral laws is also called the laws of freedom, since it refers to the laws in which freedom is possible. Thus, it can be understood that juridical law has peculiar characteristics that aim to allow freedom, and this factor permit to contain it as a subclass of moral laws, even though it is also a law that requires legality, not morality. The research also allows to conclude that juridical law and law are related to a problem that is political, but also, moral, because, they treat of question of human will, and therefore, the classification of the juridical laws within the scope of the moral laws can be justified. Besides these results, it is also possible to understand that not only the juridical law, but also the right, have a role with respect to freedom. These premises allowed to conceive that the classification of the juridical laws in the scope of the moral laws, represents that this law and the right must allow the realization of the freedom. And the purpose of this claim is that the rule of law is a space in which the moral dispositions of individuals can be developed.